Analysis of misdiagnosis and malpractice in orthopaedic traumatology: retrospective observational study of 13 cases in a teaching university hospital - Diouf, Joseph D.; Diao, Souleymane; Fall, Pape M.; Kasse, Amadou N.; Sane, Jean C. (International Journal of Research in Orthopaedics, 2025)
Orthopedics surgery has been a topic in medical malpractice for more than 130 years. The main type errors are diagnostic, treatment, communication, evaluation, environmental or system-related problems. These medical errors arouse more and more interest among our populations and degrade the doctor-patient relationship to the point of seeing more and more legal overtones. This case series presents thirteen patients with major clinical consequence resulting from a misdiagnosis or malpractice. The average age of the patients was 43.5 years. 92% of medical errors were linked to an initial admission to the emergency department. Traumatic injuries were most frequent (84,61%), including 10 cases of fractures and 1 case of dislocation. Cases of misdiagnosis were less frequent than malpractice but had serious consequences, with 1 death and 3 major amputations. Unrecognized vascular injuries remained the most common cause. The causes of malpractice are numerous. The most common main mistakes had occurred outside of operating rooms (89%) and were due to orthopaedic treatment in 67% of cases. We noted 3 cases of death related with general complications (thrombo-embolism, traumatic choc). This case series demonstrates that medical errors can be dramatic for the patients and family. Graduate medical education reform should focus on strengthening these aspects of training which can be an important factor for decreasing this phenomenon.